THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND COMPLIANCE WITH ARV (ANTIRETROVIRAL) TREATMENT PROGRAMS IN PATIENTS WITH HIV-AIDS AT THE SEROJA CLINIC RSUD DR. ADJIDARMO LEBAK YEAR 2023 - Istanti, Lilis; Isnaeni, Isnaeni (HEARTY, 2025)
Background: Human Immunodeficiency Virus (HIV) A virus that infects white blood cells, causing a decrease in the body's resistance and making it easier for infectious diseases to occur. Family support is one factor that can increase compliance in ARV treatment programs in patients with HIV-AIDS. Purpose: The aim of this research is to determine the relationship between family support and adherence to ARV treatment programs in patients with HIV-AIDS at the Seroja Clinic, RSUD dr. Adjidarmo, Lebak Regency. Methods: This research method is a type of quantitative research design cross-sectional with a non-experimental analytical design with a sample size of 58 respondents and sampling using purposive sampling techniques. The data analysis method used is test crosstab chi-square. Results: There is a significant relationship between family support and compliance in carrying out the ARV treatment program with a p-value of 0.000 (p<0.05) and with a value of Odd Ratio (OR)= 51,333. There is a relationship between emotional support and compliance with the treatment program, p=0.000 (p<0.05) OR=27,000, instrumental support with treatment program p=0,000 (p<0.05), OR= 32,667, information support with treatment programs p=0.000 (p<0.05) OR=27,000 award support with treatment program p=0.000 (p<0.05), OR=19,286 and network support with treatment programs p=0,000 (p<0.05) OR=14,000. Conclusion: There was a significant relationship between family support and compliance in carrying out the ARV treatment program. Future research is expected to examine other factors that can increase compliance in carrying out ARV treatment programs in patients with HIV-AIDS.